Investigating the Impact of Ethical Considerations in Final Assignment Submission among Postgraduate EFL Students - Alavi, Saber (Journal of Multidisciplinary in Social Sciences, 2024)
This study examined how postgraduate English as a Foreign Language (EFL) students behave and perform academically. The study demonstrates the significant impact of ethical issues on students’ behavior and outcomes by examining data from a sample of postgraduate EFL students. The results show that putting ethical concerns first encourages moral conduct, reflecting academic honesty. Students that prioritize ethics routinely create excellent work that is detailed, well-structured and follows writing rules. Additionally, ethical concerns considerably impact assignment evaluation scores, with students who practice ethics-conscious behavior scoring higher on various assessment criteria like content, organization, writing style, plagiarism, and timely submission. This research recommends that educational institutions and teachers incorporate ethical considerations into the curriculum, establish guidelines for appropriate academic behavior, and provide training programs to increase student knowledge of ethical issues to promote academic integrity. Maintaining academic standards requires the implementation of effective mechanisms to identify and manage plagiarism and other forms of academic misconduct. The results highlight the significance of creating precise regulations and procedures that spell out the repercussions of academic misconduct to promote an integrity culture inside educational institutions. Students are more likely to appreciate the importance of academic integrity and make ethical decisions throughout their educational journey when an atmosphere that emphasizes ethical behavior is fostered.